수소 기반 환원 제철 공정과 전환 기술 - 이상호; Sang-ho Yi; 이운재; Woon-jae Lee; 이영석; Young-seok Lee; 김완호; Wan-ho Kim (대한금속·재료학회지, 59(1), 2021)
This study analyzed the current state of technical development of the BF-based process, to determine ways to reduce carbon consumption. The technical features of the hydrogen reduction ironmaking process were also examined as a decarbonized ironmaking method, and related issues that should be considered when converting to hydrogen reduction are discussed. The coal rate consumed by the reduction reaction in the coal-based BF process should be less than 50%. The heat requirement for indirect reduction in hydrogen reduction is higher than that of CO reduction, since hydrogen reduction is endothermic. The BF-based integrated steel mill is an energy independent process, since coal is used for the reduction of iron ore and melting, and the by-product gases evolved from the BF process are utilized for reheating the furnace, the power plant, and steam production. For hydrogen reduction, only green hydrogen should be used for the reduction of iron ore, and the power required to melt the iron and for the downstream rolling process will have to be provided from the external grid. Therefore, to convert to hydrogen reduction, green power should be supplied from an external infrastructure system of the steel industry. It will be necessary to discuss an optimized pathway for the step-by-step replacement of current coal-based facilities, and to reach agreement on the socio-economic industrial transition to hydrogen reduction steel. (Received September 14, 2020; Accepted November 16, 2020)